The Legal Framework for Cybersecurity in Protecting E-Government Services - Baummar, Mael (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2025)
This paper examines the legal framework for cybersecurity in protecting e-government services, focusing on the sufficiency of European and German legislation. The analysis indicates that while German law effectively addresses a wide range of cybercrimes, it lacks specific provisions for enhanced penalties targeting attacks on e-government entities. The European Union's legislative framework has contributed significantly to harmonizing cybersecurity regulations across member states, however, additional advancements are necessary to address the unusual challenges faced by e-government services. Finally, the research reviews the crucial role of critical infrastructure operators.